2021
DOI: 10.3390/atmos12030319
|View full text |Cite
|
Sign up to set email alerts
|

Elevation-Dependent Trend in Diurnal Temperature Range in the Northeast China during 1961–2015

Abstract: The diurnal temperature range (DTR) is considered a signature of observed climate change, which is defined as the difference between the maximum (Tmax) and minimum temperatures (Tmin). It is well known that the warming rate of mean temperature is larger at high elevations than at low elevations in northeast China. However, it is still uncertain whether DTR trend is greater at high elevations. This study examined the spatiotemporal variation in DTR and its relationship with elevation in northeast China based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Previous studies concluded that DTR decreased in most parts of the world (Braganza et al., 2004; Zhang et al., 2021), although increased in some areas (Libanda et al., 2019). In several cases, a combination of both positive and negative trends has been observed (Liu et al., 2021; Nawaz et al., 2019; Sun et al., 2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies concluded that DTR decreased in most parts of the world (Braganza et al., 2004; Zhang et al., 2021), although increased in some areas (Libanda et al., 2019). In several cases, a combination of both positive and negative trends has been observed (Liu et al., 2021; Nawaz et al., 2019; Sun et al., 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Recent findings suggest that the increase in air temperature is likely to continue in the future decades in Iran, which could contribute to snow melting and more evaporation, negatively impacting water resources in the country, which is already facing a water crisis (Karimi Alavijeh et al., 2021). Regarding changes in surface air temperature based on 13 in situ stations, however, DTR generally provides more information on climate change than T mean because it is related to T max and T min as well as it is more sensitive to radiation energy balance change (Braganza et al., 2004; Zhang et al., 2021). Changes in DTR can also influence the start of the growing season (Huang et al., 2020), mortality and morbidity (Davis et al., 2020), and cloud cover (Libanda et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have focused on how the DTR varies over time (Easterling et al., 1997; Jaagus et al., 2014; Kumar et al., 1994; Pepin et al., 2019; Shekhar et al., 2018; Shen et al., 2014; Vose et al., 2005; Zhang et al., 2021). Comparatively, the trends of DTR in altitude were not consistent both in the open field (Gheyret et al., 2020; Rapp & Silman, 2012) and understory (Rapp & Silman, 2012; Wang et al., 2017; Xue et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the previous presented evidence suggesting on the relationship between CVD and DTR was limited, especially in northeast China where is cold weather in winter and poorer medical infrastructures. In addition, by analyzing the relationship between DTR and elevation, the existing research showed that the DTR or DTR change in northeast China is different from that in the other regions of China 28 . In Zhang et al 28 , the study results showed that in northeast China, increasing elevation has a warm effect on DTR, leading to a significant increase of the DTR trend.…”
mentioning
confidence: 99%
“…In addition, by analyzing the relationship between DTR and elevation, the existing research showed that the DTR or DTR change in northeast China is different from that in the other regions of China 28 . In Zhang et al 28 , the study results showed that in northeast China, increasing elevation has a warm effect on DTR, leading to a significant increase of the DTR trend. Thus, we focused on the city of northeast China-Hulunbuir where is area with larger diurnal temperature difference and higher CVD mortality.…”
mentioning
confidence: 99%